Economics of an export tax in the standard Keynesian framework: the case of Nigeria - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance; Vol 11 No 1 (2025): JMEF, Volume XI, Issue 1(20), Summer 2025DO - 10.14505/jmef.v11.1(20).01, 2025)
The standard textbook treatment of expansionary fiscal policy at intermediate macroeconomics level (and specifically implemented via a tax rate reduction), e.g., Blanchard (2021), Burda and Wyplosz (2023), or even at an advanced level, e.g., Romer (2018) - only considers tax cuts affecting the economy through the consumption function, by increasing the level of disposable income. Motivated by the public finance model in Nigeria, in this paper we introduce taxes on oil exports in the Keynesian cross framework and study the effects of a cut in those taxes. As expected, a cut in the export tax rate stimulates aggregate demand. There is also a multiplier effect, which we refer to the “export tax multiplier effect.” Our findings are novel in the literature and could be of interest both to policy makers, as well as economists interested in economic education and teaching.